FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KESEHATAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Priseillia Santoso, Rut Oryza; Nany, Magdalena; Suprayitno, Suprayitno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Few researches on financial distress give different results of predicting a company’ s financial distress. Financial distress is an early warning of bankruptcy, that a company has a financial failure, so that if it is not quickly well handled and getting worse, it goes to bankruptcy. The objective of this research was to give empirical evidence about the effects of net income/equity, total liabilities/total assets, sales growth, cost of goods sold/inventory, sales/account receivable, account receivable/total assets on company’s financial health both partially and simultaneously. Thirty one financial data from 31 manufacturing emitents listing at Jakarta Stock Exchange were analyzed by by multiple regression analysis. The results show that cost of goods sold/ inventory ratio significantly have positive effect on company’s financial health. Net income/equity ratio insignificantly have negative effect on company’s financial health. While total liabilities/total assets, sales growth, sales/account receivable and account receivable/total assets ratios insignificantly have positive effect on company’s financial health. The results also show that net income/ equity, total liabilities/total assets, sales growth, cost of goods sold/ inventory, sales/ account receivable, account receivable/total assets ratios have significant effect on company’s financial health.